An evaluation of the prevalence and intensity of liver fluke infection in cattle slaughtered in Jos abattoir with comments on the incidence of amphistome infection (1986)
An evaluation of the prevalence of liver fluke disease of cattle revealed an upward trend for an urban abattoir. A total of 3072 animal gall bladders were assayed between December 1980 and January 1982 and 74.06 + 6.46% were positive, the major fluke species were Fasciola gigantic and diocrocoellum hospes with a few case of schistosoma bovis. The max/min. monthly prevalence rates were 85.42% and 60.00% respectively. The mean rates for D. hospes and F. gigantic were 57.95 + 6.58% nd 48.71 + 11.66% respectively. T-test assessments showed these mean to be significantly different. The study further showed that for natural infections of cattle mixed infections were more frequent than singe infections. The mean value were 32.13% as against X single infection rates of 25.5% and 16.45% for D. hospes and F. gigantic. Chi-square analysis confirmed that mixed infection rates were significantly higher than single infections for both species. The flike species were highly prolific, producing mac egg count of 50 x 103 and 60 x 103 c.p.ml for F. gigantic and D. hospes respectively. There was variation in egg count due to seasons with significantly more eggs produced in the dry than in the wet season, for freely infected animals, there wa suppression of egg production in mixed infections which though affecting the species, had more effect on F gigantic, this resulted in significantly more eggs being produces by either species in single than in mixed infections